A pilot study about on-farm assessment of health and welfare in rabbits kept in different housing systems - Trocino, Angela; Menegon, Francesca; Zomeño, Cristina; Pasqualin, Dario; Cunial, Giovanni; Xiccato, Gerolamo; Pirrone, Fabrizio; Bertotto, Daniela; Bortoletti, Martina; Dorigo, Francesco; Lavazza, Antonio; Di Martino, Guido (Frontiers in Veterinary Science, 2022)
This pilot study tested an on-farm protocol based on resource, management, and animal-based measures to evaluate the on-farm health and welfare of rabbits kept in four different housing systems. In detail, the four housing systems were (1) standard breeding cages for reproducing does (3,300 cm2) with their litters associated with bicellular cages for growing rabbits (1,200 cm2); (2) dual-purpose cages for both reproducing does and growing rabbits (3,655 cm2); (3) enriched cages (4,739 cm2) for both reproducing does and growing rabbits equipped with a wire-mesh elevated platform (1,015 cm2); (4) parks (30,977 cm2) made up of four modules (7,744 cm2 each) joined by removing the wire net walls between them with growing rabbits kept in collective parks and reproducing does individually in the single modules. A total of 12 commercial farms (three farms/four housing systems) were visited during three seasons (summer, autumn, and winter) on two occasions each: (1) a pre-weaning visit for recordings on reproducing does and litters and (2) a pre-slaughtering visit for recordings on growing rabbits. At the pre-weaning visit, the prevalence of health concerns did not differ among does and litters kept in the different housing systems. At the pre-slaughtering visit, a higher prevalence of dermatomycosis was found in farms with dual-purpose cages and parks. Overall, taking into account the limitations due to the small sample size per housing system and the field conditions, the on-farm assessment tested in the present pilot study did not highlight major differences in the welfare and health of reproducing does and their kits as well as of growing rabbits in farms using different housing systems, which need to be confirmed on a large number of farms. The study also outlined the role of several management and environmental factors changing from one farm to another, which stresses the troubles of accounting for on-farm rabbit welfare and health exclusively to the housing system.